Soil and Water Conservation Measures in Mine Spoil Areas - Adhikari, R. N.; Rama Mohan Rao, M. S.; Pradhan, I. P.; Padmaiah, M. (Indian Forester, 1994)
The loss of soil, which constitutes one of the most important life supporting systems, results in lowering productivity and if unchecked may even threaten the very existence of life. Apart from reduction in productivity and destruction of valuable forests, it also reduces basin retention capacity causing floods in the down stream side and siltation of multipurpose reservoirs should be considered as non renewable and hence need to be protected on priority. It is therefore, essential to adopt proper conservation measures which are most effective and 1east expensive. Accordingly, studies were initiated since 1986, in two mine areas, namely (a) Navalutti Mines near Sandur (60 km from Bellary) under lease of M/s H.R.. Gaviappa & Co., and (b) Metriki Forest (Karnataka Forest Department). Vithalapuram Mine situated at 30 km on the south-west direction from Bellary.